Case report: Robotically visualized and biopsy-confirmed peritoneal carcinomatosis as initial identification of metastatic prostate adenocarcinoma in a patient with a history of prostatic urethral lift - Khan, Qateeb; Myers, Bryn; Bowar, Breann; Khan, Maryam; Mullaney, Henry; Gainey, Jordan; Schneider, Robert; Dahmoush, Laila; Nepple, Kenneth G.; Byrne, James D. (Frontiers in Oncology, 2024)
Background Peritoneal carcinomatosis is a particularly rare presentation of prostate cancer. Here we report a rare clinical case of surgically identified peritoneal carcinomatosis at the time of a planned robotic prostatectomy in a patient with a history of prostatic urethral lift procedure. Case presentation A 72-year-old man, with a history of urinary retention managed with tamsulosin, presented to his local urologist. Prostatic urethral lift procedures were performed for symptom management. After a definitive uptrend in his prostate-specific antigen (PSA) values, a biopsy was obtained, which demonstrated prostate adenocarcinoma. On presurgical multidisciplinary review, it was presumed that he had very high-risk localized prostate cancer. However, upon initiation of robotically assisted laparoscopic radical prostatectomy (RALP), he was noted to have numerous punctate white plaques on the peritoneum; biopsy of these lesions confirmed metastatic disease—for which the patient was starting on triple therapy per the PEACE-1 trial. The PSA level responded appropriately, decreasing from 16.8 to 0.08. Genetic testing was performed and returned negative for any clinically significant mutations. Conclusion Our patient, diagnosed with peritoneal carcinomatosis during a planned RALP, highlights the importance of vigilant laparoscopic exam prior to this prostatectomy. Multidisciplinary discussion is crucial for individualized and optimal treatment planning.